Digest of Technical Papers. 11th IEEE International Pulsed Power Conference (Cat. No.97CH36127)
DOI: 10.1109/ppc.1997.679311
|View full text |Cite
|
Sign up to set email alerts
|

Electropulse technology of material destruction and boring

Abstract: The fact that the dielectric strength of liquids is higher than that is for dielectric solids at the times of voltage duration less than lps was founded at Tomsk Polytechnic University at the end of the fiftieth. Fig.1 illustrates the dependence of the breakdown voltage Uw to the time of voltage acts t~ (time of voltage increasing till the coupon breakdown) for several materials. It can be of transformer oil and tap water is higher than that is for quartz, marble and sandstone to the left of volt-time characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 0 publications
2
28
0
Order By: Relevance
“…According to the numerical calculation of the plasma channel radius waveform (Figure 8c) and plasma channel expansion shockwave waveform (Figure 8d), it was found that the energy efficiency of the generator energy transformation into wave energy was about 10%. This conclusion is consistent with the conclusion that the energy efficiency of the generator energy transformation into wave energy was 10% to 20% from the breaking prediction model of electric blasting [8]. For a different insulating dielectric between electrodes and fragmented object, conversion efficiency and the correlation coefficients, such as resistance coefficient, are different [15].…”
Section: The Numerical Solution and Discussion Of The High-voltage Epsupporting
confidence: 88%
See 4 more Smart Citations
“…According to the numerical calculation of the plasma channel radius waveform (Figure 8c) and plasma channel expansion shockwave waveform (Figure 8d), it was found that the energy efficiency of the generator energy transformation into wave energy was about 10%. This conclusion is consistent with the conclusion that the energy efficiency of the generator energy transformation into wave energy was 10% to 20% from the breaking prediction model of electric blasting [8]. For a different insulating dielectric between electrodes and fragmented object, conversion efficiency and the correlation coefficients, such as resistance coefficient, are different [15].…”
Section: The Numerical Solution and Discussion Of The High-voltage Epsupporting
confidence: 88%
“…The main effect on the conversion efficiency is the equal entropy index. The high temperature of over 3 × 10 4 K [8] in the plasma channel results in a lower equal entropy index. At this time, most of the energy injected into the plasma channel was used for the formation and maintenance of the plasma channel, and a small part of the energy was converted into shockwave energy.…”
Section: The Numerical Solution and Discussion Of The High-voltage Epmentioning
confidence: 99%
See 3 more Smart Citations